Aradidae from Vietnam V. Bifurcatoaptera, a new genus of apterous Carventinae (Hemiptera: Heteroptera: Aradidae) from Vietnam - Bai, Xiaoshuan; Heiss, Ernst; Cai, Wanzhi (Zootaxa, 2018)
A new apterous genus and species of Aradidae (Hemiptera: Heteroptera), Bifurcatoaptera lamdongensis gen. et sp. nov., is described from Vietnam. The diagnostic morphological features of the new species are described and illustrated.